Bulbotrachystola, a substitute name for Centruroides Breuning, 1940 (Coleoptera Cerambycidae) - Vitali, Francesco; Yanega, Doug (Zootaxa, 2019)
The genus name Centruroides was first introduced by George Marx (in Howard, 1889: 211) for two species of scorpions in the family Buthidae: C. exilicauda (Wood, 1863) and C. luctifer n. sp. The latter species, coming from Indefatigable Is. (Galapagos), lacks a description and has been considered as a nomen nudum and synonym of Centruroides exsul (Meise, 1934) (Lambertz, 2013). Nonetheless, exilicauda Wood (Buthus) is an available and valid species name; thus, Centruroides is available according to the ICZN, 1999, Art. 12.2.5. (“the specific name or names can be unambiguously assigned to a nominal species-group taxon or taxa”).